2009
DOI: 10.1111/j.1745-4573.2009.00145.x
|View full text |Cite
|
Sign up to set email alerts
|

CONTROL OF LISTERIA MONOCYTOGENES ON FRANKFURTERS WITH ANTIMICROBIALS AND HYDRODYNAMIC PRESSURE PROCESSING*

Abstract: The antilisterial activity of sodium diacetate and pediocin (ALTA 2341) on frankfurters was evaluated in combination with hydrodynamic pressure processing (HDP). Minimum inhibitory concentration (MIC) of these strains as determined in tryptic soy broth was 0.4% and >600 AU/mL, for sodium diacetate and ALTA 2341, respectively. Frankfurters were surface inoculated with a five‐strain mixture of Listeria monocytogenes after dipping in (1) control (sterile water); (2) 5% sodium diacetate; (3) 3% ALTA 2341(P1); (4) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Sharma et al (2008) compared the inactivation of foodborne viruses by HDP or HPP and found that both technologies significantly reduced foodborne viruses on sausages. The combination of nisin and HDP processing showed 2 log reduction for L. monocytogenes in frankfurters compared to control samples (Patel, Sanglay, & Solomon, 2009). …”
Section: Yerisinia Enterocoliticamentioning
confidence: 95%
“…Sharma et al (2008) compared the inactivation of foodborne viruses by HDP or HPP and found that both technologies significantly reduced foodborne viruses on sausages. The combination of nisin and HDP processing showed 2 log reduction for L. monocytogenes in frankfurters compared to control samples (Patel, Sanglay, & Solomon, 2009). …”
Section: Yerisinia Enterocoliticamentioning
confidence: 95%
“…The MBCs of LAE against L. monocytogenes TSULM1 and S. Rissen TSUSR1 were both 0.032 mg/ml, or four-and two-fold, respectively, higher than the corresponding MIC (Table 1). Earlier studies found MIC of SD, SC, SL, and LAE against L. monocytogenes in the range of 4.00-5.00 mg/ml 36,37 , 70 mg/ml 38 , 2.5-4.8% (v/v) [38][39][40] , and 0.0125-0.025 mg/ml 9, 41 , respectively.…”
Section: Susceptibility Testmentioning
confidence: 99%
“…Frankfurters surfaces are typically contaminated by microorganisms, including L. monocytogenes, after the cooking process and prior to packaging. There are many intervention technologies that can be used to inactivate foodborne pathogens on pre-cooked sausage and ready-to-eat meat products including antimicrobials [8] high pressure processing [12], infrared light [13], in-package thermal treatments [14], ionizing radiation [15], ultraviolet light [6], pulsedlight [16], etc. While many technologies are available to improve the microbiological safety and shelf-life of precooked sausages, those actually in commercial use are relatively few because of the need for effectiveness, low cost, and the ability to use the technology at commercial processing line speeds.…”
Section: Introductionmentioning
confidence: 99%